Changes in Level of the Conus after Corrective Surgery for Scoliosis: MRI-Based Preliminary Study in 31 Patients - Hong, Jae-Young (The Korean Orthopaedic Association, 2011)
BACKGROUND: Detection of postoperative spinal cord level change can provide basic information about the spinal cord status, and electrophysiological studies regarding this point should be conducted in the future. METHODS: To determine the changes in the spinal cord level postoperatively and the possible associated factors, we prospectively studied 31 patients with scoliosis. All the patients underwent correction and posterior fusion using pedicle screws and rods between January 2008 and March 2009. The pre- and postoperative conus medullaris levels were determined by matching the axial magnetic resonance image to the sagittal scout image. The patients were divided according to the change in the postoperative conus medullaris level. The change group was defined as the patients who showed a change of more than one divided section in the vertebral column postoperatively, and the parameters of the change and non-change groups were compared. RESULTS: The mean pre- and postoperative Cobb's angle of the coronal curve was 76.80° ± 17.19° and 33.23° ± 14.39°, respectively. Eleven of 31 patients showed a lower conus medullaris level postoperatively. There were no differences in the pre- and postoperative magnitude of the coronal curve, lordosis and kyphosis between the groups. However, the postoperative degrees of correction of the coronal curve and lumbar lordosis were higher in the change group. There were also differences in the disease entities between the groups. A higher percentage of patients with Duchene muscular dystrophy had a change in level compared to that of the patients with cerebral palsy (83.3% vs. 45.5%, respectively). CONCLUSIONS: The conus medullaris level changed postoperatively in the patients with severe scoliosis. Overall, the postoperative degree of correction of the coronal curve was higher in the change group than that in the non-change group. The degrees of correction of the coronal curve and lumbar lordosis were related to the spinal cord level change after scoliosis correction.